Identification of novel proteins associated with movement-related adverse antipsychotic effects by integrating GWAS data and human brain proteomes. (November 2022) - Li, Jiqing; Pang, Jicheng; Si, Shucheng; Zhang, Kai; Tang, Fang; Xue, Fuzhong
Highlights: Multiple novel proteins may be involved in MAAE, such as GRIN2B, ADRA1A, and PED4B. Several pathways may be associated with MAAE, such as glutamatergic synapse and glutamate receptor complex. MAAE may share protein targets with PD and PD's motor symptoms, such as PTK2B and SLC4A5. Abstract: Genome-wide association studies (GWAS) have identified some variants for movement-related adverse antipsychotic effects (MAAE), while how these variants confer MAAE remains unclear. We used the probabilistic Mendelian randomization (PMR) method to identify candidate proteins for MAAE by integrating MAAE GWASs and protein quantitative trait loci (pQTL) data. An independent pQTL data from the Banner project and brain-derived eQTL data were used to perform confirmatory PMR. A total of 56 proteins were identified as candidate targets for MAAE after false discovery rates (FDR) correction, such as GRIN2B, ADRA1A, and PED4B. 12 genes were replicated in the confirmatory PMR, and 18 genes had consistent evidence at the transcript level. Furthermore, we investigated the associations between candidate proteins and the motor symptoms of Parkinson's disease (PD). There were 24, 38, and 10 candidate proteins that were significantly associated with PD, PD motor subtypes, and PD motor progression, respectively. Enrichment analysis identified 34 GO terms and 17 pathways that may be involved in MAAE, such as glutamatergic synapse, glutamate receptor complex, and GABAergic synapse. Our study identified multiple candidate genes and pathways that were associated with MAAE, providing new insights into the biological mechanism of MAAE and targets for further mechanistic and therapeutic studies.